Analisis Pembiayaan Dan Profitabilitas Bank Pada Bank Umum Syariah Di Indonesia - A Aryati; Faisal Faisal (Jurnal Penelitian Ekonomi Manajemen dan Bisnis, 2023)
This research aims to analyze the profitability of Sharia Banks in Indonesia. The research variables consist of: murabahah, musyarakah and ijarah financing. The test results showed that the F test showed that the values in the regression model of the murabahah, musyarakah and ijarah variables together had an effect on the profitability variable with a sig value of 0.000. Sig value. 0.000 < 0.05 and Fcount value 12.826 > Ftable 2.74. Likewise, with the partial test, murabahah, musyarakah and ijarah financing partially influence the profitability of sharia commercial banks in Indonesia. To increase bank profitability, efforts are needed to increase murabahah, musyarakah and ijarah financing. However, the principle of prudence and risk control is required for each of the burdens incurred. So that the profitability target will increase in the future.